2015
DOI: 10.1212/wnl.0000000000002169
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged perivascular spaces and small diffusion-weighted lesions in intracerebral hemorrhage

Abstract: In our cohort, high EPVS, in particular CSO-EPVS, and larger hematoma volume emerged as independent predictors for SA-DWIL after ICH. Our findings might provide a new explanation for the pathophysiologic mechanisms predisposing to SA-DWIL after ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 28 publications
1
65
1
Order By: Relevance
“…In our cohort, we observed acute ischaemic lesions among 15.5% of patients with acute ICH within 10 days after symptom onset. These results are in line with the prevalence reported in previous studies, ranging from 11% to 41% . As previously described, we found that patients with lobar ICH more frequently had DWI lesions than those with deep ICH .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort, we observed acute ischaemic lesions among 15.5% of patients with acute ICH within 10 days after symptom onset. These results are in line with the prevalence reported in previous studies, ranging from 11% to 41% . As previously described, we found that patients with lobar ICH more frequently had DWI lesions than those with deep ICH .…”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms and etiology of DWI lesions in patients with acute ICH remain uncertain. Previous studies have linked DWI lesions to underlying SVD . DWI lesions are more frequently observed in CAA‐ICH and are associated with markers of CAA including lobar CMB, WMHs and enlarged perivascular spaces in the centrum semiovale .…”
Section: Discussionmentioning
confidence: 99%
“…As for EPVSs, Wu et al . using a cohort in America found that CSO‐EPVSs were significantly more prevalent in ICH patients with R‐DWILs than in those without and identified a trend between high basal ganglia EPVSs (BG‐EPVSs) and the presence of R‐DWILs . Conversely, a similar trend between BG‐EPVSs and the presence of R‐DWILs was not identified in this work.…”
Section: Discussioncontrasting
confidence: 65%
“…[5][6][7][8][9][10] Over the last several years, a growing number of studies have characterized the presence and frequency of ischemic lesions remote from the acute hematoma visualized on diffusion-weighted imaging (DWI) in patients with primary ICH undergoing MRI. [11][12][13][14][15][16][17][18][19] Across these series, remote DWI lesions are visualized in 11%-41% of patients. There have been conflicting reports of an association between DWI lesions and large fluctuations in BP in the acute hospital setting.…”
mentioning
confidence: 87%
“…Finally, one recent report linked DWI lesions to enlarged perivascular spaces, a variable that we did not evaluate. 19 However, compared to prior studies, strengths of this study include the large sample size, the multicenter, prospective study design, and inclusion of an equal number of participants from multiple races and ethnicities, particularly those at higher risk of ICH; these study design characteristics increase the generalizability of the study results compared to prior studies.…”
mentioning
confidence: 98%